Duodenal CD8+ T resident memory cell apoptosis contributes to gut barrier dysfunction and microbial translocation in early alcohol‐associated liver disease in humans. Issue 6 (2nd August 2022) - Maccioni, Luca; Loriot, Axelle; Dewulf, Joseph; Bommer, Guido; Horsmans, Yves; Lanthier, Nicolas; Leclercq, Isabelle; Schnabl, Bernd; Stärkel, Peter
Summary: Background: Intestinal T cells are key in gut barrier function. Their role in early stages of alcohol‐associated liver disease (ALD) remain unknown. Aim: To explore the links between intestinal T cells, microbial translocation and ALD Methods: Patients with alcohol use disorder (AUD) following a rehabilitation programme were compared to subjects with non‐alcoholic fatty liver disease (NAFLD) and healthy controls. Clinical and laboratory data (liver stiffness, controlled attenuation parameter, AST, ALT, K18‐M65) served to identify AUD patients with isolated steatosis (minimal liver disease) or steatohepatitis/fibrosis (ALD). Serum microbial translocation markers were measured by ELISA, duodenal and plasma levels of sphingolipids by targeted LC–MS. T lymphocytes in duodenal biopsies were characterised by immunohistochemistry, flow cytometry and RNA sequencing on FACS‐sorted cells. Mechanisms for T‐cell alterations were assessed in vitro . Results: Patients with ALD, but not those with minimal liver disease, showed reduced numbers of duodenal CD8+ T resident memory (TRM) cells compared to controls or patients with NAFLD. TRM transcriptomic analysis, in vitro analyses and pharmacological inhibition of cathepsin B confirmed TRM apoptosis driven by lysosomal membrane permeabilisation and cathepsin B release into the cytosol. Altered lipid metabolism and increased duodenal and plasma sphingolipids correlated with apoptosis. Dihydroceramide dose‐dependently reduced viability of TRM. Duodenal TRM phenotypic changes, apoptosis and transcriptomic alterations correlated with increased levels of microbial translocation markers. Short‐term abstinence did not reverse TRM cell death in patients with ALD. Conclusions: Duodenal CD8+ TRM apoptosis related to functional changes in lysosomes and lipid metabolism points to impaired gut adaptive immunity specifically in patients with AUD who developed early ALD. Abstract : Graphical summary of the study design and principal results.